2011
DOI: 10.1007/s10067-011-1879-y
|View full text |Cite
|
Sign up to set email alerts
|

Primary biliary cirrhosis in a rheumatoid arthritis patient treated with rituximab, a case-based review

Abstract: Primary biliary cirrhosis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 30 publications
0
4
0
2
Order By: Relevance
“…Respecto al curso de la CBP ante el uso de rituximab para indicación de AR encontramos 4 casos 7,8,12 . Sargin y cols.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Respecto al curso de la CBP ante el uso de rituximab para indicación de AR encontramos 4 casos 7,8,12 . Sargin y cols.…”
Section: Discussionunclassified
“…Debido a que la paciente seguía con alta actividad de la AR le indicaron abatacept. La CBP continuó quiescente 7 . La justificación de la utilización de terapias depletoras anti-CD20 no está muy clara, pero los autores describen la participación de las células B en la patogenia de la CBP e incluso reportes de pacientes con CBP con respuesta subóptima al ácido ursodesoxicólico, que tratados con rituximab mejoraron los parámetros bioquímicos hepáticos 12 .…”
Section: Discussionunclassified
“…Recently, the anti-CD20 monoclonal antibody rituximab was suggested as a treatment option for PBC [8, 11]. Biological and immunological improvements, such as of biliary enzyme, serum IgM and serum AMA titer, have been reported [8, 11]. However, histological improvement has not been reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study showed that rituximab was as safe and well-tolerated in patients with PBC as in patients with other indications, suggesting that rituximab has a potential therapeutic effect in this subgroup of patients without optimal responses to UDCA [5]. Another case reported on a 50-year-old patient with RA and PBC who was treated with rituximab and showed clinical and laboratory improvement in the first six months of treatment [12]. In our patient, we used a small amount of MTX (7.5mg/week) combined with two doses of 1000mg of rituximab, two weeks apart.…”
Section: Discussionmentioning
confidence: 99%